The reality of using distance e-learning by special education teachers in Jeddah Governorate in light of the Corona pandemic - Al-Qahtani, Mohammed Rashid (Journal of Educational and Psychological Sciences, 2022)
The aim of the current research is to identify the reality of the use of distance e-education among teachers of special education in light of the Corona pandemic, and to reveal the obstacles to the use of distance e-education among these teachers in light of the Corona pandemic, and to identify the main trends they have towards the use of distance e-learning In light of this pandemic, and also to know their point of view on the use of distance e-learning for people with special needs. And the research problem appeared and was identified in the following question: What is the reality of the use of distance education by special education teachers in light of the Corona pandemic from their point of view? The research tool was applied to a random sample representing the research community, and the Robert Mason equation was used to determine the most appropriate sample size according to the size of the community. , with an arithmetic average ability of (4.27), and the extent of the obstacles to the use of distance education by special education teachers in light of the Corona pandemic was “ok”, with an arithmetic average of ability (3.87), and the extent of the attitudes of teachers of special education towards the use of distance e-learning in light of the pandemic. The Corona pandemic was OK, with an arithmetic average of (3.95), and one of the recommendations recommended by researchers is to train special education teachers to use various distance e-learning techniques, and the need for the Ministry of Education to work on developing e-learning systems and making them available to teachers and students, and encouraging teachers For their students to use distance e-learning, provide the digital infrastructure necessary to operate e-learning at a distance, and work to provide educational design models that fit the nature of e-learning remotely in special education.